Pre-Eclampsia and Intrauterine Growth Restriction (IUGR)Prevention– Is Enoxaparin an Effective Option - Saeed, Saira; Barkat, Shafia; Murtaza, Badar (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the effectiveness of Enoxaparin in preventing pre-eclampsia and intrauterine growth restriction in women with the history of pre-eclampsia and IUGR in an earlier pregnancy.Study Design: Quasi-Experimental Study.Place and Duration of Study: Department of Obstetrics and Gynaecology, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Mar to Sep 2019.Methodology: In this study, a total of 186 pregnant females of age 20-40 years with >6 ± 0 and